Calligonum caput-medusae seedlings adapt to drought stress through changing chlorophyll fluorescence parameters - Huo, Haixia; Jaffar, Muhammad Tauseef; Zhang, Jianguo; Shang, Jianxuan (Frontiers in Plant Science, 2025)
Understanding plants responses to drought stress is crucial for selecting appropriate species for shelter-forest construction in arid and semi-arid regions. Calligonum caput-medusae, one of the most planted shrubs along the Taklimakan Desert Highway Shelterbelt (TDHS), contributes significantly to maintaining the highway’s ecological stability. This study aimed to investigate the physiological responses of biennial C. caput-medusae seedlings to drought stress by monitoring changes in soil moisture and chlorophyll fluorescence parameters [actual photo chemical efficiency of PSII (Y(II)), unregulated energy dissipation quantum yield (Y(NO)), non-photochemical quenching coefficient (NPQ), and regulatory energy dissipation quantum yield (Y(NPQ))] under controlled conditions. The results showed that soil moisture declined progressively with prolonged drought stress. Although the photosystem II (PSII) reaction centers of the seedlings experienced some stress after 30 days of drought, no irreversible photodamage occurred. However, the risk of photoinhibition and damage to the photosynthetic apparatus increased with prolonged drought, as evidenced by an increase in NPQ. These findings suggest that C. caput-medusae seedlings adapt to drought stress by modulating their chlorophyll fluorescence characteristics, enhancing our understanding of its drought adaptation mechanisms and highlighting the need for future research on its long-term physiological responses under field conditions and varying drought intensities.